Analisis Pelayanan Pendampingan Anak Korban Kekerasan Seksual Di Pusat Pelayanan Terpadu Pemberdayaan Perempuan Dan Anak Kabupaten Garut - Agustina, Novi; Kania, Ikeu; Sofiyani, Dafi Nur Awaliah (Program Pasca Sarjana Universitas Garut, 2022)
Cases of violence against women, even children, often make headlines in the media. But much has yet to be revealed. There are so many cases of violence against children, but only a few are followed up. This research analyzes the assistance of the Women's Empowerment and Child Protection Integrated Service Center (P2TP2A) for child victims of sexual violence in Garut Regency. This study found that the handling of cases of violence against children at the Integrated Services Center for Women's Empowerment and Child Protection (P2TP2A) was in accordance with the standard operating procedures stipulated in the Regulation of the State Minister for Women's Empowerment and Child Protection Number 5 of 2010. Data collection in this study was carried out with library research and field studies in the form of observations, interviews and documentation. The results of the research Assistance services for Children Victims of Sexual Violence at P2TP2A Garut in its implementation have been going quite well according to the four indicators of excellent assistance services, namely the presence of service providers, service recipients, type of service and customer satisfaction.The assistance services in the District P2TP2A continue to run as expected.